USING E-LEARNING TO PREVENT INFORMATIONAL STRESS OF EMPLOYEES WORKING REMOTELY - Oleksandra Pinchuk; Nataliia I. Pinchuk; Olena I. Bondarchuk; Valentyna V. Balakhtar; Kateryna S. Pavlenok (Інформаційні технології і засоби навчання)
The article deals with the problem of remotely working employees' informational stress caused by crisis conditions in Ukraine. The article analyzes the features of e-learning important for preventing informational stress among remotely working employees. The following specific features of informational stress, by their information impact, are highlighted: 1) features associated with information overload, 2) features associated with human interaction with information technology, and 3) features associated with professional activities.